PENGOBATAN TRADISIONAL MASYARAKAT BANJAR DALAM PERSPEKTIF TASAWUF - Muhammad Aminudin; Ahmad Ahmad (TASHWIR, 2025)
The batatamba tradition of the Banjar people is not merely a form of traditional healing but a living manifestation of Islamic spirituality that unites the body, soul, and divine consciousness. This study aims to explore the Sufi meanings embedded within batatamba as a holistic healing model that continues to thrive amid the rise of modern medicine. Using a qualitative descriptive-reflective approach, the research combines participant observation, personal reflection, and in-depth interviews with patamba (traditional healers) and patients. The findings reveal that practices such as bapidara, batutungkal, minta banyu, batimung, manyamak, and baurut are not limited to physical therapy but embody spiritual dimensions of dhikr (remembrance of God), tawakkul (trust in God), tazkiyatun nafs (purification of the soul), and barakah (divine blessing), fostering inner peace and closeness to Allah Swt. The integration of Sufism and traditional medicine positions batatamba as a symbol of harmony between knowledge and faith, humanity and nature. Core values such as tawhid (divine unity), sincerity, compassion, and spiritual awareness reflect that batatamba is not simply a healing act, but a spiritual journey toward balance and wholeness. Thus, this tradition stands as a valuable heritage of Islam Nusantara deeply relevant for modern society in its search for true health: a state of physical well-being and spiritual serenity. Keywords: Banjar Sufism, Batatamba, Traditional Healing, Islamic Spirituality, Holistic Health